Hydrogenation of biomass pyrolysis oil using enhanced reduction catalytic capacity cellular by expressing excavated carbonyl reductase. (15th January 2023) - Bu, Chongyang; Qiao, Hui; Zou, Lihua; Tao, Yuanming; Fu, Jiaming; Liu, Chao; Zheng, Zhaojuan; Ouyang, Jia
Graphical abstract: Highlights: Excavating carbonyl reductase with broad substrate spectrum and high activity. Improve the cell tolerance and reduction to biomass pyrolysis oil inhibitors. A biphasic biocatalytic system for biomass pyrolysis oil was established. Reduction of ketone-aldehydes to alcohol in bio-oil by microorganisms. Abstract: A biocatalytic method to achieve the hydromodification of biomass fast pyrolysis oil was implemented. Two carbonyl reductases SDR-1 and SDR-8 were excavated in the genome of Bacillus coagulans NL01, enhanced Escherichia coli ability to tolerate and reduce various toxic ketone aldehydes. 10 g/L furfural and 8 g/L acetoin as bio-oil model compounds could be transformed by the recombinant E. coli SDR-1 and E. coli SDR-8 respectively. The biphasic catalysis system was constructed to convert the keto-aldehyde compounds in bio-oil to the corresponding alcohol at 30 °C. Recombinant E. coli SDR-8 could completely consume 20 g/L glucose and consume 60% 20 g/L glucose in the diluted 50-fold and 30-fold bio-oil catalytic system, respectively. This provided a new pathway for the hydrogenation of bio-oil by biocatalytic method and laid the foundation for the low-temperature esterification in the later stage.